2016
DOI: 10.3389/fnsys.2016.00060
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Short Social Training on Prosocial Behaviors: An fMRI Study

Abstract: Efficient brain–computer interfaces (BCIs) are in need of knowledge about the human brain and how it interacts, plays games, and socializes with other brains. A breakthrough can be achieved by revealing the microfoundations of sociality, an additional component of the utility function reflecting the value of contributing to group success derived from social identity. Building upon our previous behavioral work, we conduct a series of functional magnetic resonance imaging (fMRI) experiments (N = 10 in the Pilot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 76 publications
0
2
0
1
Order By: Relevance
“…The fNIRS results showed that the basketball athletes had stronger INS in the dorsolateral prefrontal area in the cooperative task. Previous studies have shown that the dorsolateral prefrontal lobe is involved in cognitive control ( Sanfey et al, 2003 ; Gabay et al, 2014 ; Feng et al, 2015 ), and plays an important role in cooperation-related decision-making ( Fermin et al, 2016 ; Lukinova and Myagkov, 2016 ; Macoveanu et al, 2016 ). When dyads choose to cooperate, the dorsolateral prefrontal area is more sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…The fNIRS results showed that the basketball athletes had stronger INS in the dorsolateral prefrontal area in the cooperative task. Previous studies have shown that the dorsolateral prefrontal lobe is involved in cognitive control ( Sanfey et al, 2003 ; Gabay et al, 2014 ; Feng et al, 2015 ), and plays an important role in cooperation-related decision-making ( Fermin et al, 2016 ; Lukinova and Myagkov, 2016 ; Macoveanu et al, 2016 ). When dyads choose to cooperate, the dorsolateral prefrontal area is more sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…Moving in that direction, in previous investigations of competition (or cooperation) dynamics, the presence of an external feedback informing participants on their performance—in particular when it is positive—proved to be able to modulate their behavioral responses [ 17 , 26 28 ]. While it has been suggested that even such modulation may be mediated by dorsolateral prefrontal structures [ 29 ], potential effects of processing information conveyed by performance feedbacks on inter-brain neural synchronicity and inter-agents synergies are yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…En el tronco se identifican investigaciones teóricas, en las que se analiza: la racionalidad, la confianza, las interacciones sociales y los componentes hormonales que intervienen en la toma de decisiones, al igual que investigaciones que estudian el cerebro, identificando la brecha entre la depresión y la recompensa social (Mellick et al, 2015;Scheele et al, 2013). Lo anterior, sin dejar de lado el estudio de cómo las relaciones sociales afectan la actividad funcional y la conexión con otras áreas del cerebro, resaltando que la socialidad facilita la cooperación, la equidad y la provisión (Lee & Harris, 2013;Lukinova & Myagkov, 2016).…”
Section: Elección Socialunclassified